Surface Functionalization of Upconversion Nanoparticle for Biological Usage - Devi Wahyuningtyas; Hsien-Ming Lee; Hua-De Gao (IPTEK Journal of Proceedings Series, 2015)
Upconversion nanoparticle (UCNP) coated with uniform silica shells, which were further functionalized with poly(ethylene glycol) (PEG) and (3-aminopropyl)triethoxysilane (APTES), produces water dispersible core-shell structured UCNPs with average hydrodynamic size around 100 nm. The hydrothermal treatment to the particle stabilize amines of APTES on the surface of UCNPs. The stable and positive zeta potential also prove that the amines is successfully attached on the particle’s surface, with good stability in colloidal solution. We also discovered that hydrothermal treatment temperature over 200 oC diminish the luminescence properties of UCNPs.